ROLE OF UNIVERSITIES IN DEVELOPMENT AND TRANSFORMATION OF REGIONAL EDUCATION - Сав'юк, Лариса Олександрівна (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
In the article are analysed modern being, problems and prospects of development of the system of regional school and special secondary education and its communication with universities. Resulted results of statistical researches of level of knowledges of students which study on the department of computer technologies in the control systems and automation of the Ivano-Frankivs’k national technical university of oil and gas. The conducted researches allow the necessity of introduction of the regional program of the controlled from distance support of schools of the Precarpathian region in the region of increase of level of knowledges from of informative-communication technologies.